Strategic management & leadership from an Islamic perspective - Ahmad, Khaliq (Arabic Book and Culture Days, 2018)
The Islamic approach to strategic management and leadership as an emerging discipline - often referred to as Islamic management - which deals with the corporate governance and management of organizations from the perspective of the knowledge acquired from the revealed and other Islamic sources of knowledge and results in applications compatible with the Islamic beliefs and practices that are shariah compliant